Thermoelectric efficiency enhancement in ScN-based multilayers by Nb diffusion-driven doping - Joris More-Chevalier; Urszula D. Wdowik; Jiří Martan; Xavier Portier; Stanislav Cichoň; Esther de Prado; Petr Levinský; Ladislav Fekete; Jan Pokorný; Dejan Prokop; Petr Hruška; Markéta Jarošová; et al. (Applied Surface Science Advances)
The thermoelectric properties of ScN/Sc1-xNbxN multilayers deposited on MgO (001) substrates were studied using a combined experimental and theoretical approach based on density functional theory. Four ScN/Sc1-xNbxN multilayers with varying doped layer thicknesses were produced, resulting in an overall Nb atomic percentage in the samples of 0.4 %, 1.2 %, 1.8 %, and 4.8 %, respectively. Structural characterization confirmed the epitaxial growth of multilayers with sharp interfaces. Raman spectroscopy revealed a redshift of optical phonon modes with increasing Nb concentration. Temperature-dependent Raman measurements showed an irregular shift in transverse optical (TO) modes, while longitudinal optical (LO) modes experienced a blueshift, indicating complex phonon dynamics influenced by temperature and multilayer structure. Thermoelectric measurements indicated an increase in the Seebeck coefficient and a decrease in thermal conductivity with Nb-doped ScN interlayers. The figure of merit (ZT) potentially increased to over 0.3. This improvement highlights the potential of this approach for enhancing the thermoelectric performance of scandium nitride.